Analisis Pengaruh Penggunaan Uang Digital Terhadap Jumlah Uang Yang Beredar Di Indonesia - Adeliya Saragih; Muhammad Irwan Padli Nasution (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the effect of the use of digital money on the amount of money circulating in Indonesia. The method used is Library Research (Library) in this writing, this method uses books, and journals, both written and online. Based on this research, it can be concluded that the use of digital money brings efficiency in transactions, reduces operational costs, allows fast payments, and allows better transaction tracking. It changes the way we interact with finance, providing benefits to individuals, businesses, and the economy as a whole. However, it should be noted that security, regulation, and consumer protection are also important concerns in the development of this financial technology.